STAT5 regulation of BCL10 parallels constitutive NFκB activation in lymphoid tumor cells - Mitra Abhisek (Molecular Cancer, 2009)
Abstract Background Signal Transducer and Activator of Transcription 5 A and B (STAT5) are key survival factors in cells of the lymphoid lineage. Identification of novel, tissue-specific STAT5 regulated genes would advance the ability to combat diseases due to aberrant STAT5 signaling. In the present work a library of human STAT5 bound genomic elements was created and validated. Results Of several STAT5 responsive genomic regulatory elements identified, one was located within the first intron of the human BCL10 gene. Chromatin immuno-precipitation reactions confirmed constitutive in vivo STAT5 binding to this intronic fragment in various human lymphoid tumor cell lines. Interestingly, non-phosphorylated STAT5 was found in the nuclei of Kit225 and YT cells in the absence of cytokine stimulation that paralleled constitutive NFκB activation. Inhibition of the hyperactive JAK3/STAT5 pathway in MT-2 cells via the Mannich-base, NC1153, diminished the constitutive in vivo occupancy of BCL10-SBR by STAT5, reduced NFκB activity and BCL10 protein expression in a dose dependent manner. Moreover, depletion of STAT5 via selective antisense oligonucleotide treatment similarly resulted in decreased BCL10 mRNA and protein expression, cellular viability and impaired NFκB activity independent of IL-2. Conclusion These results suggest that the NFκB regulator BCL10 is an IL-2-independent STAT5 target gene. These findings proffer a model in which un-activated STAT5 can regulate pathways critical for lymphoid cell survival and inhibitors that disrupt STAT5 function independent of tyrosine phosphorylation may be therapeutically effective in treating certain leukemias/lymphomas.